Changes in histone H3 lysine 36 methylation in porcine oocytes and preimplantation embryos. - Yun Fei Diao (Public Library of Science (PLoS), 2014)
Histone H3 lysine 36 (H3K36) methylation is known to be associated with transcriptionally active genes, and is considered a genomic marker of active loci. To investigate the changes in H3K36 methylation in pig, we determined the mono-, di-, and tri-methylations of H3K36 (H3K36me1, H3K36me2 and H3K36me3, respectively) in porcine fetal fibroblasts, oocytes and preimplantation embryos by immunocytochemistry using specific antibodies and confocal microscopy. These analyses revealed that only H3K36me3 in porcine fetal fibroblasts consistently colocalized with transcription sites identified as actively synthesizing RNA based on fluorouridine (FU) incorporation. Treatment of cells with flavopiridol, which blocks transcription elongation, completely abrogated both H3K36me3 signals and RNA synthesis. All three types of H3K36 methylation were present and did not significantly differ during oocyte maturation. In parthenogenetic embryos, H3K36me1 and -me2 were detected in 1-cell through blastocyst-stage embryos. In contrast, H3K36me3 was not detected in most 1-cell stage embryos. H3K36me3 signals became detectable in 2-cell stage embryos, peaked at the 4-cell stage, decreased at the 8-cell stage, and then became undetectable at blastocyst stages in both parthenogenetic and in vitro-fertilized (IVF) embryos. Unlike the case in IVF embryos, H3K36me3 could not be demethylated completely during the 1-cell stage in somatic cell nuclear transfer (SCNT) embryos. These results collectively indicate that H3K36me3, but not H3K36me1 or -me2, is associated with transcription elongation in porcine fetal fibroblasts. H3K36me3 is developmentally regulated and may be a histone mark of embryonic gene activation in pig. Aberrant H3K36 tri-methylation occurred during the nuclear reprogramming of SCNT embryos.